Right ventricular cavity near obliteration in neonatal severe biventricular hypertrophic cardiomyopathy. (21st October 2014) - Jivanji, Salim GM; Daubeney, Piers; Franklin, Rodney; Sheppard, Mary
Abstract : A newborn presenting with cyanosis at day 9 of life was admitted to the local hospital. Initial local echocardiography confirmed a cardiac issue and the patient was transferred to a tertiary cardiac hospital. Further imaging confirmed a rare presentation of cardiomyopathy with severe right ventricular outflow tract obstruction. Surgery was performed but with postoperative haemodynamic instability complicated by incessant ventricular tachycardia. Following discussion with the family, care was withdrawn. Postmortem demonstrated a rare form of hypertrophic cardiomyopathy with right ventricular outflow tract obstruction not previously described in a neonate.